Peran Lembaga Tudang Sipulung dalam Pengelolaan Usaha Tani di Kabupaten Bone - Firdayanti, Firdayanti (UNIVERSITAS NEGERI MAKASSAR, 2019)
The results of this study show that: 1) there are no differences in the implementation of tudang sipulung at the district, sub-district and village level, except the participants. Thoseattending the village level are POKTAN, village extension officers, village security apparatus, POPT sub-district, Irrigation Department, in the Districts drained GAPOKTAN in all Sub-Districts, Sub-District Heads, security apparatus, PU. Irrigation,and POPT. The District Level presents stakeholders from the province and representatives from 27 sub-districts including the head of sub-district, POKTAN, PPL, Pananrang, corporate partners, experts and stakeholders. 2) Pananrang uses the calculation of the moon cycle, i.e. Muharram, observes natural phenomena and synchronizes between the phenomena with the Sipariamacalendar (an eight-year of the Hijri calendar) and the Gregorian calendar. 3) The problems resolution of tudang sipulung are the slow and less seed distribution so that the farmers undertake an initiative to provide themselves under the guidance of PPL, rare and expensivefertilizers, irrigation and pests. 4) The results of Pananrang and BMKG prediction are: the rain for the wet season (April-September) is almost the same related to the beginning planting season, i.e. the fourth week of April - early August, major pests are stem borer, planthopper and rats, the technology applied are direct seed planting tools, transplanterand direct planting in managing rice fields and seed varieties used per sector are ciliwungin the Bone Kota sector; IR 66, Ciliwung and inpari 30 in Bone West sector;inpari 30 in Bone Selatan sector; mekongga, sentani 14, ciliwung and inpari 30 in Bone Timursector; ciliwung, inpari 30, inpari 33 and cigelis in Bone Utara sector.